Landscape of N6-Methyladenosine Modification Patterns in Human Ameloblastoma - Niu, Xing; Xu, Jingping; Liu, Jinwen; Chen, Lijie; Qiao, Xue; Zhong, Ming (Frontiers in Oncology, 2020)
Objective To comprehensively analyze the global N6-methyladenosine (m6A) modification pattern in ameloblastoma. Methods m6A peaks in ameloblastoma and normal oral tissues were detected by MeRIP-seq. Differentially methylated m6A sites within messenger RNAs (mRNAs), long no-coding RNA (lncRNAs) and circular RNA (circRNAs) were identified, followed by functional enrichment analysis. By comprehensively analyzing MeRIP-seq and RNA-seq data, differentially expressed mRNAs, lncRNAs and circRNAs containing differentially methylated sites were identified. RNA binding proteins (RBPs) were then identified for differentially methylated m6A sites. Results In total, 3,673 differentially methylated m6A sites within coding genes were detected, of which 16.2% (704/3,673) were significantly upmethylated sites in ameloblastoma compared to normal oral tissues. Furthermore, 4,975 differentially methylated m6A sites within lncRNAs were identified, of which 29.4% (1,465/4,975) were upmethylated sites in ameloblastoma. We also found 364 differentially methylated m6A sites within circRNAs, of which 22.5% (82/364) were upmethylated sites in ameloblastoma. Differentially methylated m6A was most often harbored in the CDS (54.10%), followed by 5’UTR (21.71%). Functional enrichment analysis revealed that m6A modification could be involved in the development of ameloblastoma by organism developmental processes. A total of 158 RBPs within differentially methylated m6A sites were identified, which were significantly involved in mRNA metabolic process, mRNA processing, RNA processing, RNA splicing and RNA transport. Conclusion Our findings for the first time provide m6A landscape of human ameloblastoma, which expand the understanding of m6A modifications and uncover regulation of lncRNAs and circRNAs through m6A modification in ameloblastoma.